2021
DOI: 10.3390/safety7030060
|View full text |Cite
|
Sign up to set email alerts
|

Visual Perception and Understanding of Variable Message Signs: The Influence of the Drivers’ Age and Message Layout

Abstract: Variable message signs (VMS) are used to display messages providing up-to-date traffic-relevant information so that drivers can safely adapt their behavior in real time. The information reported in a VMS should be brief but comprehensive to minimize perception time. The latter can be influenced by the way the message is displayed. This study investigates how the different ways of displaying the same message can influence reading time and the information perception process at different driving speeds. Specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The most crucial human factor in improving driver cognitive ability is the driver's driving experience [29] . Meanwhile, as the level of information increases, gender will begin to affect drivers' cognitive abilities [30] .…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…The most crucial human factor in improving driver cognitive ability is the driver's driving experience [29] . Meanwhile, as the level of information increases, gender will begin to affect drivers' cognitive abilities [30] .…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…The aim was to optimize the positioning of advanced guidance signs within mountainous road tunnels [60]. Using eye-tracking techniques, parameters related to drivers' eye-tracking characteristics were extracted, allowing for an analysis of the effects of drivers' age and the information layout on visual perception and comprehension of variable message symbols [61].…”
Section: Eye-tracking Technology Application For Sign Layout Optimiza...mentioning
confidence: 99%
“…(3) Processing of sign information stage In the processing of sign information stage, the processing and cognitive ability of information (PCAI) are the key issues [79]. The long average duration of AOI (ADA) of gaze behavior indicates that this area contains complex information, and recognition is difficult [61]. Hence, PCAI can be described using the ADA, which reflects the time drivers spend processing the information.…”
Section: Selection Of Evaluation Indicatorsmentioning
confidence: 99%
“…This consideration points out an important issue in terms of occupational safety and risk communication, especially in light of the increasing cultural diversity among construction workers who often migrated to work in countries different from their own 6 . Some studies have also found that the sign comprehension time increased with participant age and the number of information units and was shorter for male counterparts 12 , 13 . Ben-Bassat et al and Jiang et al showed that older adults may have particular difficulty in understanding high complexity and low comprehensibility signs due developing physical and cognitive constraints 14 , 15 .…”
Section: Introductionmentioning
confidence: 97%